Desain Model Pengendalian Kualitas produk Radiator berbasis Six Sigma dan Acceptance Sampling - Paduloh, Paduloh; Pratama, Akbar Adjie; Salsabila, Annisa Ayu (Universitas Negeri Gorontalo, 2025)
PT KJI is a manufacturing company engaged in the production of car radiators. The quality of the products is the main focus to meet customer standards. The company faces a high Defect rate that exceeds the tolerance limit of 3%, affecting both process efficiency and customer satisfaction. This study aims to identify the root causes of product defects, calculate the sigma level, and design improvements to reduce the defect rate. The Six Sigma method with a DMAIC approach is used to analyse and control the quality of the production process, supported by the application of acceptance sampling based on AQL standards. The analysis covers the production process, inspection systems, and machine maintenance conditions. It was found that the lack of inspection on incoming materials and finished products, as well as irregular maintenance schedules, are the main factors contributing to the high defect rate. Proposed improvements include enhancing inspections of incoming and outgoing products according to AQL and implementing a more consistent machine maintenance schedule. After the implementation of the proposed improvements, there was a significant reduction in the number of Cacative products. The average sigma level increased from 3.8 to 4.7. This improvement had a positive impact on product quality, production process efficiency, and the reliability of the quality control system at PT KJI.